Incidence Rate and Patterns of Physical Restraint Use Among Adult Patients in Malaysia - Eskandari, Fatemeh; Abdullah, Khatijah Lim; Zainal, Nor Zuraida; Wong, Li Ping (SAGE Publications, 2018)
Incidence rate and patterns of physical restraint use were examined based on a cross-sectional study in 22 wards of a large teaching hospital in Malaysia. Results indicated that the highest rate of physical restraint (19.7%) was reported from neurology–neurosurgery wards. “Un-cooperative for electroconvulsive therapy” and “trying to pull out catheters” were the most commonly reported reasons to use restraint in psychiatric and non-psychiatric wards, respectively. There were some relationships between patterns of physical restraint in this study. Exploring the incidence rate and patterns of physical restraint is important so that effective strategies can be formulated to minimize using restraint in hospitals.